2006
DOI: 10.2172/889442
|View full text |Cite
|
Sign up to set email alerts
|

How Accurately Can We Calculate Neutrons Slowing Down In Water ?

Abstract: DISCLAIMERThis document was prepared as an account of work sponsored by an agency of the United States Government. Neither the United States Government nor the University of California nor any of their employees, makes any warranty, express or implied, or assumes any legal liability or responsibility for the accuracy, completeness, or usefulness of any information, apparatus, product, or process disclosed, or represents that its use would not infringe privately owned rights. Reference herein to any specific co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Note that a proper S(α, β) bound thermalization treatment was included for H 2 O (with a free gas model applied to all other nuclides). Without any thermal scattering (stationary), neutrons continue to slow down in energy and never form a thermal spectrum, while in contrast, using free atom scattering (proper bound or free gas model), the spectrum diverges from this continuous slowing down and eventually forms a Maxwellian-like thermal spectrum [27]. In the event, the S(α, β) treatment was not found to have any noticeable effect on reaction rates because, in the absorption reactions considered here, the giant resonances generally occurred at slightly higher neutron energies than those influenced by it, which are below 4 eV [26].…”
Section: Self-shielding Effectmentioning
confidence: 99%
“…Note that a proper S(α, β) bound thermalization treatment was included for H 2 O (with a free gas model applied to all other nuclides). Without any thermal scattering (stationary), neutrons continue to slow down in energy and never form a thermal spectrum, while in contrast, using free atom scattering (proper bound or free gas model), the spectrum diverges from this continuous slowing down and eventually forms a Maxwellian-like thermal spectrum [27]. In the event, the S(α, β) treatment was not found to have any noticeable effect on reaction rates because, in the absorption reactions considered here, the giant resonances generally occurred at slightly higher neutron energies than those influenced by it, which are below 4 eV [26].…”
Section: Self-shielding Effectmentioning
confidence: 99%
“…In earlier studies comparing results from a variety of neutron transport codes each using whatever neutron data it felt to be appropriate, we found a spread in even the simple integral parameters, such as K-eff, in excess of 1 % [4]. In earlier comparisons of MERCURY and TART we found that by having both codes use the same neutron data, namely TART's data, the differences in Keff could be reduced to less than 0.1% [7], indicating that most of the differences between codes is due to differences in nuclear data. In this study both codes are again using the same TART data and same physics models, so we expect results to be at the same 0.1 % or better level.…”
Section: Integral Resultsmentioning
confidence: 99%
“…In particular we want to verify the free atom scattering treatment in MERCURY as used over an extended temperature range; by comparison to many other codes for TART this has already been verified over many years [4,7].…”
Section: Objectivesmentioning
confidence: 99%
“…They modify the energy and angular distributions of secondary neutrons. A description of the model for water is given in references [24,25], and studies that investigate how we can accurately calculate neutrons slowing down in water are reported in reference [26]. The double differential incoherent inelastic scattering cross-section of a single bound atom in molecule (H bound in H 2 O) can be written as a function of the symmetric scattering law S(a,b):…”
Section: Governing Equationsmentioning
confidence: 99%